Radio el Prado y su Influencia en la Radiodifusión de Riobamba Durante el Periodo 1925-1980. - Alvarez Moreno, Maria Augusta (2012)
Radio El Prado, founded in Riobamba, on february 27, 1925, officially began broadcasting June 13, 1929, becoming the first radio station installed in Riobamba and Ecuador. Its creator, Engineer Carlos Cordovez Borja, not only has the merit of being the first ecuadorian broadcaster, but also was the inventor of several radio devices, among which stand out the transmitter itself with which radio El Prado came air. Research conducted thereon, are historical narratives, however there is a study about incident that actually took radio El Prado in local and national broadcasting. This text is an academic research that aims to determine the influence exerted on Radio El Prado development of broadcasting in Riobamba and Ecuador during the years following its creation, and rescue the historical and cultural value of the business conducted by the Engineer Carlos Cordovez, through his radio station.